2019
DOI: 10.3390/genes10120947
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Analysis of the lncRNA and mRNA Transcriptome Revealed Genes and Pathways Potentially Involved in the Anther Abortion of Cotton (Gossypium hirsutum L.)

Abstract: Cotton plays an important role in the economy of many countries. Many studies have revealed that numerous genes and various metabolic pathways are involved in anther development. In this research, we studied the differently expressed mRNA and lncRNA during the anther development of cotton between the cytoplasmic male sterility (CMS) line, C2P5A, and the maintainer line, C2P5B, using RNA-seq analysis. We identified 17,897 known differentially expressed (DE) mRNAs, and 865 DE long noncoding RNAs (lncRNAs) that c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 89 publications
(108 reference statements)
2
20
0
Order By: Relevance
“…2c and d). This phenomenon has also been observed in humans, Sus scrofa, Populus and Gossypium hirsutum [30,34,[72][73][74]. In addition, in the study of maize and red clover, fusion events tended to arise inter-chromosomally rather than intra-chromosomally [22,24].…”
Section: Discussionmentioning
confidence: 64%
“…2c and d). This phenomenon has also been observed in humans, Sus scrofa, Populus and Gossypium hirsutum [30,34,[72][73][74]. In addition, in the study of maize and red clover, fusion events tended to arise inter-chromosomally rather than intra-chromosomally [22,24].…”
Section: Discussionmentioning
confidence: 64%
“…More and more studies had shown that miRNAs play key roles in host‐pathogen interactions by regulating the expression of host immune genes or viral genes, affecting viral replication (Chawla & Sokol, 2011; Kang et al, 2018; Mead & Tu, 2008; Padmanabhan et al, 2009; Simón‐Mateo & García, 2006). Studies have also confirmed that cellular miRNAs and viral miRNAs contribute to host immunity and host–pathogen interaction by regulating the expression of host or pathogen‐related genes in various organisms (Y. Li, Qin, et al, 2019; Ryan & Williams, 2019; Wu et al, 2013, 2016).…”
Section: Discussionmentioning
confidence: 92%
“…Studies have also confirmed that cellular miRNAs and viral miRNAs contribute to host immunity and host-pathogen interaction by regulating the expression of host or pathogen-related genes in various organisms (Y. Li, Qin, et al, 2019;Ryan & Williams, 2019;Wu et al, 2013Wu et al, , 2016.…”
Section: Discussionmentioning
confidence: 93%
“…Anther development is a multistage and complex process that determines yield and quality of most of the industrial crops. This process is controlled by a complex network of numerous genes [ 24 , 25 ]. With a plethora of plant genomes now sequenced, -omics driven technologies are playing a significant role in the study of the regulatory mechanism of anther development [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAs are unravelling as key regulators of plant development [ 50 ], and their role in plant sexual reproduction has been confirmed. For example, lncRNAs related to sexual reproduction have been systematically identified in Gossypium hirsutum [ 24 ], Hordeum vulgare [ 35 ] and Brassica rapa [ 15 ], but their role in the development of male buds of C. oleifera had still remained unknown. Here, we have identified a total of 414 putative lncRNAs in three different development stages of C. oleifera anthers by RNA-seq.…”
Section: Discussionmentioning
confidence: 99%